NOTE ON THE LENGTH-WEIGHT RELATIONSHIP OF KALBASU, LABEO CALBASU (HAM.) - Chatterji, Anil; Ali, M; Mumtaz, Asfa (Indian Journal of Fisheries, 2011)
Since Labeo calbasu (Ham.), a major freshwater carp, constitutes an important fishery of the river Kali, the length-weight relationship and its application to some of biological aspects of the species was studied.